De l’axiologie - Muriel Verbeeck-Boutin (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The choices in conservation and restoration are based on pre-eminent values. In literature as in the action, the reference to Riegl and Brandi has become classic: in particular the use of aesthetic and historical instances. However, contemporary art as well as conservation applied to collections other than art claims other valid criteria. The author proposes to develop a system of values, where the concerns of various actors in the conservation and restoration could be explicitly articulated. It is indeed important to objectify decisions of intervention.